Cultural conversions : unexpected consequences of Christian missionary encounters in the Middle East, Africa, and South Asia - Sharkey, Heather J. (Heather Jane), 1967- (Syracuse, New York : Syracuse University Press, 2013)
"Essays in this volume study unforeseen cultural conversions that arose from missionary activities in the Middle East, Africa, and South Asia during the nineteenth and twentieth centuries.
Introduction: the unexpected consequences of Christian missionary encounters / Heather J. Sharkey -- Conflicting conversions and unexpected Christianities in Central Africa / David M. Gordon -- Church versus country: Palestinian Arab Episcopalians, nationalism, and revolt, 1936-39 / Laura Robson -- Missionaries and ethnography in the service of litigation: Hindu law and Christian custom in India's Deccan, 1750-1863 / Chandra Mallampalli -- Hybridity, parody, and contempt: Buddhist responses to Christian missions in Sri Lanka / Stephen C. Berkwitz -- The Port Said orphan scandal of 1933: colonialism, Islamism, and the Egyptian welfare state / Beth Baron -- Robert Moffat and the invention of Christianity in South Africa / Paul S. Landau -- Missionaries and the making of colonial notables: conversions to modernity in Eritrea and Ethiopia, 1890-1935 / James De Lorenzi -- The scholar-missionaries of the Basel Mission in southwest India: language, identity, and knowledge in flux / Mrinalini Sebastian -- The gospel in Arabic tongues: British Bible distribution, evangelical mission, and language politics in North Africa / Heather J. Sharkey.
Includes bibliographical references (pages 225-306) and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Missions -- Middle East; Missions -- Africa; Missions -- South Asia; Christianity -- Influence; Christianity and culture; Christianity and politics; Christianity -- Influence; Christianity and culture; Christianity and politics; Missions -- Africa; Missions -- Middle East; Missions -- South Asia; RELIGION -- Christian Ministry -- Missions; Christianity and culture; Christianity and politics; Christianity -- Influence; Missions; Africa; Middle East; South Asia; Mission; Kulturkontakt; Kulturvermittlung; SOCIAL SCIENCE / Essays; Electronic books